Building collective power in citizen-led initiatives for health accountability in Guatemala: the role of networks - Alison Hernández; Anna-Karin Hurtig; Isabel Goicolea; Miguel San Sebastián; Fernando Jerez; Francisco Hernández-Rodríguez; Walter Flores (BMC, 2020)
Abstract Background Citizen-led accountability initiatives are a critical strategy for redressing the causes of health inequalities and promoting better health system governance. A growing body of evidence points to the need for putting power relations at the forefront of understanding and operationalizing citizen-led accountability, rather than technical tools and best practices. In this study, we apply a network lens to the question of how initiatives build collective power to redress health system failures affecting marginalized communities in three municipalities in Guatemala. Methods Network mapping and interpretive discussions were used to examine relational qualities of citizen-led initiatives' networks and explore the resources they offer for mobilizing action and influencing health accountability. Participants in the municipal-level initiatives responded to a social network analysis questionnaire focused on their ties of communication and collaboration with other initiative participants and their interactions with authorities regarding health system problems. Discussions with participants about the maps generated enriched our view of what the ties represented and their history of collective action and also provided space for planning action to strengthen their networks. Results Our findings indicate that network qualities like cohesiveness and centralization reflected the initiative participants' agency in adapting to their sociopolitical context, and participants' social positions were a key resource in providing connection to a broad base of support for mobilizing collective action to document health service deficiencies and advocate for solutions. Their legitimacy as "representatives of the people" enabled them to engage with authorities from a bolstered position of power, and their iterative interactions with authorities further contributed to develop their advocacy capabilities and resulted in accountability gains. Conclusions Our study provided evidence to counter the tendency to underestimate the assets and capabilities that marginalized citizens have for building power, and affirmed the idea that best-fit, with-the-grain approaches are well-suited for highly unequal settings characterized by weak governance. Efforts to support and understand change processes in citizen-led initiatives should include focus on adaptive network building to enable contextually-embedded approaches that leverage the collective power of the users of health services and grassroots leaders on the frontlines of accountability.